2021
DOI: 10.1007/s40843-020-1627-4
|View full text |Cite
|
Sign up to set email alerts
|

Co-delivery of chemotherapeutic drugs and cell cycle regulatory agents using nanocarriers for cancer therapy

Abstract: Combination chemotherapy is widely exploited to overcome multidrug resistance (MDR) and enhance the therapeutic effect of anti-tumor agents clinically. The traditional combination regimens applied in clinical practice still suffer from various obstacles, such as inevitable side effects. Fortunately, the application of nanotechnology and the proposal of co-delivery systems make the combination therapy more effective. The occurrence, development, and metastasis of tumors are closely related to the cell cycle. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 158 publications
0
13
0
Order By: Relevance
“…According to the mechanism at the molecular level, chemotherapeutic drugs can be divided into four categories: alkylating agents, nucleotide reductase inhibitors and their anti-metabolites, antibiotics, and anti-tumor plant drugs [22,23]. There are dozens or even hundreds of drugs in each class.…”
Section: Mechanism Of Chemotherapeutic Drugsmentioning
confidence: 99%
“…According to the mechanism at the molecular level, chemotherapeutic drugs can be divided into four categories: alkylating agents, nucleotide reductase inhibitors and their anti-metabolites, antibiotics, and anti-tumor plant drugs [22,23]. There are dozens or even hundreds of drugs in each class.…”
Section: Mechanism Of Chemotherapeutic Drugsmentioning
confidence: 99%
“…104,105 Conventional cancer chemotherapy, radiotherapy, and surgery can cause serious side effects. 106 The quality of life of cancer patients declines. 107 Because of its LMW, relatively simple structure, strong tumor selectivity, few adverse reactions, easy absorption, diverse routes of administration, and low risk of inducing multidrug resistance, polypeptides have attracted widespread attention in cancer-related fields.…”
Section: Anticancer Peptidesmentioning
confidence: 99%
“…Cancer is a disease with high morbidity and mortality, which constitutes a serious health burden and a global economic burden 104,105 . Conventional cancer chemotherapy, radiotherapy, and surgery can cause serious side effects 106 . The quality of life of cancer patients declines 107 .…”
Section: Peptides With Different Functionsmentioning
confidence: 99%
“…Selectins are C-type lectins that bind to properly modified glycan ligands, such as CD44, Eselectin ligand-1, CD43, CD34, or addresses with a variable specificity. For example, the study by Hao et al showed that both CD147 and CD44 are involved in cancer drug resistance [25]. CD44 is a multifunctional protein involved in cell adhesion, migration and drug resistance, with a critical role in cell signaling and cell-ECM interactions in cancer.…”
Section: Multidrug Resistance Of the Tumor Microenvironmentmentioning
confidence: 99%